Controlling Gas-Phase Reactions for Efficient Charge Reduction Electrospray Mass Spectrometry of Intact Proteins - Frey, Brian L. (2005)
Charge reduction electrospray mass spectrometry (CREMS) reduces the charge states of electrospray-generated ions, which concentrates the ions from a protein into fewer peaks spread over a larger m/z range, thereby increasing peak separation and decreasing spectral congestion. An optimized design for a CREMS source is described that provides an order-of-magnitude increase in sensitivity compared to previous designs and provides control over the extent of charge reduction. Either a corona discharge or an α-particle source was employed to generate anions that abstract protons from electrosprayed protein cations. These desired ion/ion proton transfer reactions predominated, but some oxidation and ion-attachment reactions also occurred leading to new peaks or mass-shifted broader peaks while decreasing signal intensity. The species producing these deleterious side-reactions were identified, and conditions were found that prevented their formation. Spectrometer m/z biases were examined because of their effect upon the signal intensity of higher m/z charge-reduced protein ions. The utility of this atmospheric pressure CREMS was demonstrated using a cell lysate fraction from E. coli. The spectral simplification afforded by CREMS reveals more proteins than are observed without charge reduction.